One Stop Cafe / Tajul Arif Mohd Shukor ... [et al.] - Mohd Shukor, Tajul Arif; Hassan, Muhd Hamidi; Nazamuddin, Nizad Norman; Abu Bakar, Hafizulamin (Faculty of Hotel and Tourism Management, 2004)
Our natured of business is in food Services. One Shop Cafe represents a cafe with the motoring sports concept. Our restaurant will be serving varieties of food especially western style for the customers